A Methodological Review of Piezoelectric Based Acoustic Wave Generation and Detection Techniques for Structural Health Monitoring - Zhigang Sun; Bruno Rocha; Kuo-Ting Wu; Nezih Mrad (International Journal of Aerospace Engineering)
Piezoelectric transducers have a long history of applications in nondestructive evaluation of material and structure integrity owing to their ability of transforming mechanical energy to electrical energy and vice versa. As condition based maintenance has emerged as a valuable approach to enhancing continued aircraft airworthiness while reducing the life cycle cost, its enabling structural health monitoring (SHM) technologies capable of providing on-demand diagnosis of the structure without interrupting the aircraft operation are attracting increasing R&D efforts. Piezoelectric transducers play an essential role in these endeavors. This paper is set forth to review a variety of ingenious ways in which piezoelectric transducers are used in today’s SHM technologies as a means of generation and/or detection of diagnostic acoustic waves.